Orolaelaps (Acari: Mesostigmata: Melicharidae): description of two new species, redescription of Orolaelaps quisqualis and new characterisation of the genus - Sourassou, Nazer Famah; Moraes, Gilberto Jose; Santos, Jandir Cruz (Zootaxa, 2015)
Until now, the genus Orolaelaps De Leon was known only from the USA. Two new species of this genus, namely Orolaelaps piracicabensis n. sp. and Orolaelaps tupiniquim n. sp., are described from specimens collected in the State of  São Paulo, Brazil. Orolaelaps quisqualis De Leon, the type species of the genus, is redescribed and an updated diagnosis of Orolaelaps is provided.